Identification of sodium channel isoforms that mediate action potential firing in lamina I/II spinal cord neurons - Hildebrand, Michael E (BioMed Central, 2011)
BACKGROUND: Voltage-gated sodium channels play key roles in acute and chronic pain processing. The molecular, biophysical, and pharmacological properties of sodium channel currents have been extensively studied for peripheral nociceptors while the properties of sodium channel currents in dorsal horn spinal cord neurons remain incompletely understood. Thus far, investigations into the roles of sodium channel function in nociceptive signaling have primarily focused on recombinant channels or peripheral nociceptors. Here, we utilize recordings from lamina I/II neurons withdrawn from the surface of spinal cord slices to systematically determine the functional properties of sodium channels expressed within the superficial dorsal horn. RESULTS: Sodium channel currents within lamina I/II neurons exhibited relatively hyperpolarized voltage-dependent properties and fast kinetics of both inactivation and recovery from inactivation, enabling small changes in neuronal membrane potentials to have large effects on intrinsic excitability. By combining biophysical and pharmacological channel properties with quantitative real-time PCR results, we demonstrate that functional sodium channel currents within lamina I/II neurons are predominantly composed of the Na(V)1.2 and Na(V)1.3 isoforms. CONCLUSIONS: Overall, lamina I/II neurons express a unique combination of functional sodium channels that are highly divergent from the sodium channel isoforms found within peripheral nociceptors, creating potentially complementary or distinct ion channel targets for future pain therapeutics.